A phase I trial evaluating the safety, tolerability, pharmacokinetics and pharmacodynamics of intravenously administered low-anticoagulant heparin (M6229) in critically ill sepsis patients - van Mourik, Niels; van Amstel, Rombout B. E.; Slim, Marleen A.; van Vught, Lonneke A.; van der Poll, Tom; Huckriede, Joram; de Vries, Femke; de Kimpe, Sjef J.; Crabbé, Raf; van Leeuwen, Simone J. M.; Ekhart, Peter F.; Reutelingsperger, Chris P. M.; et al. (Intensive care medicine experimental, 2025)
Background Histones released in response to cellular injury are important mediators of organ failure and death in sepsis. Preclinical studies demonstrate that neutralization of histones in sepsis is associated with improved outcome. M6229 is a low-anticoagulant heparin able to neutralize histones. We aimed to evaluate the safety, tolerability, pharmacokinetics and pharmacodynamics of M6229 in critically ill patients with sepsis. Methods This was a first-in-human, phase I, monocenter trial in patients with sepsis admitted to the intensive care unit (ICU). Patients received a single 6 h intravenous infusion of M6229. A modified continual reassessment method (mCRM) with escalation overdose control was used for dose-escalation. The model was based on the probability of activated partial thromboplastin time (aPTT) being above 90 s (i.e., dose limiting pharmacologic event, DLPE). Three cohorts were studied (1: 0.15 mg/kg/h; 2: 0.45 mg/kg/h; 3: 0.90 mg/kg/h). Results Ten patients were included. The aPTT increased proportionally with increasing dosages of M6229 and decreased rapidly after infusion cessation. One DLPE occurred (aPTT of 100 s). Based on the mCRM model and data safety monitoring board recommendations, the maximum tolerated dose was defined as 0.9 mg/kg/h for a 6 h infusion of M6229. No serious adverse events were related to study drug infusion. An increase in QTc was probably related to infusion in one patient. M6229 showed close to dose-proportional pharmacokinetics. Total histone H3 and H2b plasma levels increased during and/or in the hours after M6229 infusion in all patients. In four out of five patients with plasma samples positive for histone H3, proteolytic cleavage was observed after infusion start. A decrease in sequential organ failure assessment score was observed in the days after infusion in 70% of patients. Conclusions M6229 was deemed safe to use in critically ill sepsis patients. Our results suggest intravascular neutralization of histones by M6229. Future clinical studies need to confirm our findings and the efficacy of M6229 .